A Theoretical Review: Globalization and Preventing Premarital Sex - Ishak, Sitti Nurhidayanti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Globalization is a double-edged sword since it improves human efficiency and effectiveness along with the development of technology. However, the negative impacts of globalization hit developing countries hard, such as the fading of traditional culture and people's tendency to be dependent on  developed countries, or people imitate the negative behavior of those living in developed countries. Aims: This paper conceptualizes premarital sex behavior, which is a problem in the social environment that occurs in Indonesian society and generally in Islamic countries. The author will reveal sexual problems experienced by adolescents in terms of social phenomena in modern times. In addition, the impact of adolescent sexual behavior before marriage will also be discussed in this article, both in social, cultural, and religious settings. The author also offers alternative solutions to prevent premarital sex behavior in adolescents by looking at the role of the family, social environment, and educational institutions. Method: We use the Theory of Planned Behavior and Social Learning Theory approaches to explore the direction of adolescent behavior in making decisions. Results: As a result, our model can contribute to future research to research adolescent premarital sex behavior, especially in countries affected by globalization. In addition, we also offer a research model by formulating several propositions that will be a guide for further research. Conclusion: Globalization is very influential and we feel it in everyday life. Conditions such as promiscuity, negative internet, premarital sex, etc. can be found in social life. This condition cannot be avoided, which is something that should happen and needs to be addressed wisely by the whole community, especially parents who have teenage children. Several alternatives are offered to overcome this problem, among others, through educational institutions, the role of the family, and the social environment. These three factors are an alternative to preventing adolescent associations that lead to premarital sex.